Evaluation of the bean qualities of cocoa clones after propagated from somatic embryogenesis culture - G., Entuni; H., Nori; R., Edward; M.J., Ahmad Kamil; N.A, Rahman (2020)
A series of field experiments were conducted to assess the bean qualities of elite cocoa clones (KKM4, KKM22, MCBC1, and PBC230) after regenerated through somatic embryogenesis culture and grafting. The bean of all clones was morphologically and physically evaluated before quantified for the physiochemical changes after the fermentation and drying processes. No abnormalities were found in the morphological characteristics of beans for all treatments. However, the KKM4 clone of immature zygotic embryo culture yielded distinctly different lightest individual seed fresh weight (4.13 g), shortest seed length (21.2 mm), and seed width (11.5 mm) compared with those from the staminode culture and grafting. From this study, some clones such as KKM4 exhibited variation after propagated from different types of explants during somatic embryogenesis culture. Nevertheless, the dried bean moisture content (7.31%) and cut test score (685.0), which fall within the standard range, validated that the bean quality is not affected after the somatic embryogenesis culture process.